Bresson, Becker, Audiard e la dimensione del carcere. Annotazioni su Un condamné à mort s’est échappé (1956), Le Trou (1960) e Un Prophète (2009) - Roberto Chiesi (DNA Di Nulla Academia, 2023)
Un condamné à mort s’est échappé or Le vent souffle ou il veut (1956), by Robert Bresson, Le Trou (1960) by Jacques Becker and Un Prophète (2009) by Jacques Audiard, are three films where the prison dimension is not a narrative device at the service of striking and adventurous actions, but constitutes a universe where we witness the radicalization of some human dynamics, a form of dramatic condensation that it reveals the qualities, potentials and miseries of human beings, thanks to the conditions of coercion and the claustrophobia in which the characters are forced to live.